Spiritual intelligence and its relationship to orientation towards life among graduate students at King Abdulaziz University in Jeddah Saudi Arabia - Alshahrani, Sami Abdullah (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the level of spiritual intelligence, orientation towards life and the relationship between them among a sample of graduate students at King Abdulaziz University, and The relational descriptive approach was used, and the research sample reached 356 students selected from the research community of approximately 3000 students, , and the researcher used the integrated spiritual intelligence scale for each of Amram & Dryer in his summary form the Arabization and codification of Bushra Ismail Ahmad (Arabization and legalization of Bushra Ismail Ahmed, 2013), scale (Abd al-Latif and Hamada, 1998; Hamdan, 1999; Dakka, 2010) A measure of orientation towards life, and the results showed that there is a complete correlation between The two variables, The recommendations were to hold training workshops that develop the spiritual intelligence of students, and educational courses that enhance their positive view about the topic of orientation towards life.
Keywords: spiritual intelligence; orientation towards life; Graduate students